2020
DOI: 10.1016/j.neuroimage.2020.117086
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood deprivation, prefrontal morphology and neurocognition in late childhood to early adolescence

Abstract: Background: Neighborhood deprivation adversely effects neurodevelopment and cognitive function; however, mechanisms remain unexplored. Neighborhood deprivation could be particularly impactful in late childhood/early adolescence, in neural regions with protracted developmental trajectories, e.g., prefrontal cortex (PFC). Methods: The Adolescent Brain Cognitive Development (ABCD) study recruited 10,205 youth. Geocoded residential history was used to extract individual nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 90 publications
(135 reference statements)
7
83
0
Order By: Relevance
“…They also found that Ecological stress, amygdala reactivity, and internalizing problems higher neighborhood poverty was negatively associated with scores across all seven cognitive domains. Likewise, Vargas et al, (2020) reported that neighborhood deprivation, as measured by ADI quantiles (1-5; five being the highest deprivation), was negatively related to cognitive function and that this association was partially mediated by PFC surface area. Although all of these analyses considered cross-sectional associations, it will be important to consider how SES and brain associations change across time --a strength of the ABCD design.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They also found that Ecological stress, amygdala reactivity, and internalizing problems higher neighborhood poverty was negatively associated with scores across all seven cognitive domains. Likewise, Vargas et al, (2020) reported that neighborhood deprivation, as measured by ADI quantiles (1-5; five being the highest deprivation), was negatively related to cognitive function and that this association was partially mediated by PFC surface area. Although all of these analyses considered cross-sectional associations, it will be important to consider how SES and brain associations change across time --a strength of the ABCD design.…”
Section: Discussionmentioning
confidence: 95%
“…Although all of these analyses considered cross-sectional associations, it will be important to consider how SES and brain associations change across time --a strength of the ABCD design. Furthermore, although the brain was identified as mediator in cross-sectional analyses of the ABCD sample (Assari, 2020;Assari et al, 2020;Vargas et al, 2020), it will be important to reexamine the mechanistic role of specific brain regions using the longitudinal ABCD data to distinguish between cross-sectional and longitudinal effects. Finally, to describe how SES manifests in the brain (Farah, 2017) and relates to cognitive and behavioral outcomes, future work should examine differences in the analytic pipeline that contribute to convergence and differences in findings.…”
Section: Discussionmentioning
confidence: 99%
“…As described in detail by Casey et al (2018), participants completed a high-resolution T1-weighted structural MRI scan (1-mm isotropic voxels) using scanners from Philips Healthcare (Philips, Andover, Massachusetts, USA), GE Healthcare (General Electrics, Waukesha, WI, USA), or Siemens Healthcare (Siemens, Erlangen, Germany) [ 72 ]. All the structural MRI data were processed using FreeSurfer version 5.3.0, available at http://surfer.nmr.mgh.harvard.edu/ [ 80 , 81 ], according to standard processing pipelines [ 72 ]. Processing included removal of nonbrain tissue, segmentation of gray and white matter structures [ 82 ], and cortical parcellation [ 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…All the structural MRI data were processed using FreeSurfer version 5.3.0 (B. Fischl, Sereno, & Dale, 1999;Vargas, Damme, & Mittal, 2020), in line with the standard processing pipelines (Casey et al, 2018). The process included the removal of nonbrain tissue, the segmentation of gray and white matter (Bruce Fischl et al, 2002) and the parcellation of the cerebral cortex (Bruce Fischl et al, 2004).…”
Section: Measures and Measurementsmentioning
confidence: 99%